OF THE OPTIMAL IRON CONTENT IN THE FEMALE MILK SUBSTITUTES - T.N. Sorvacheva; E.A. Pyr'eva; E.N. Kozhevnikova ("Paediatrician" Publishers LLC, 2008)
The article provides for the literature based data on why the optimal iron content in the formula to feed the infants is essential. Lately, there has been a trend to reduce the level of iron in the adapted milk formulas. The prerequisites for that are the new data on iron metabolism peculiarities and diagnostic criteria for the iron deficient states among infants, as well as the development of the new generation of the female milk substitutes with a wider range of the iron content in the formulas offered by different producers.Key words: infants, feeding, iron deficiency.